2013
DOI: 10.1055/s-0033-1358682
|View full text |Cite
|
Sign up to set email alerts
|

Neuroenhancement among Swiss Students – A Comparison of Users and Non-Users

Abstract: Introduction: This survey aims to contribute to the current discussion about neuroenhancement by comparing cognitive enhancer(s) (CE) users with CE non-users with a focus on their characteristics and attitudes. Methods: An online survey was sent out to all undergraduate and graduate students of the University of Z?rich who allow such e-mails (n=8?642), accompanied by advertisement for the survey in lectures. 1?765 students completed the survey, which was about healthy people?s use of Ritalin, Adderall and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
50
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(63 citation statements)
references
References 18 publications
10
50
1
2
Order By: Relevance
“…Distributive justice is one of the cardinal concerns of the enhancement debate, mentioned as an important issue by nearly all commentators [22,23,57]. One interpretation of our results is that they contradict a large body of empirical research focused on concerns regarding inequality of access to pharmacological CAS enhancement [22,46,[58][59][60][61][62][63][64]. It is worth noting that the key difference between our results and these previous studies is that participants were unprompted as to potential causes of their discomfort towards the use of pharmacological CAS enhancement.…”
Section: The Public Endorses Fair Distribution Of Mental Capitalmentioning
confidence: 86%
“…Distributive justice is one of the cardinal concerns of the enhancement debate, mentioned as an important issue by nearly all commentators [22,23,57]. One interpretation of our results is that they contradict a large body of empirical research focused on concerns regarding inequality of access to pharmacological CAS enhancement [22,46,[58][59][60][61][62][63][64]. It is worth noting that the key difference between our results and these previous studies is that participants were unprompted as to potential causes of their discomfort towards the use of pharmacological CAS enhancement.…”
Section: The Public Endorses Fair Distribution Of Mental Capitalmentioning
confidence: 86%
“…Although the hypothetical enhancement technologies presented in the Pew study (synthetic blood transfusions, brain chip implants, gene editing) are far more invasive than tDCS, this study-which found that consumers of tDCS devices are less religious than the US population-suggests that religiosity may be a factor in individual willingness to adopt even less invasive enhancement technologies such as tDCS. Indeed, a study comparing Swiss student users of cognitive enhancement drugs to non-users found that a higher percentage of users were not affiliated with any religion, and that more users than non-users rated religion as Bnot important^ (Ott and Biller-Andorno 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have examined the demographics, motivations, and attitudes of those who utilize cognitive enhancement drugs (e.g., Eickenhorst et al 2012;Ragan et al 2013;Forlini et al 2014;Ott and Biller-Andorno 2014;Vargo and Petróczi 2016;Riddell et al 2017), there is little data to-date on similar measures for those who utilize brain stimulation devices marketed for cognitive enhancement. In addition, while many studies on the use of cognitive enhancement drugs have focused on local populations, often comprised of university students, the methodology employed here allowed for the examination of a unique sample that cut across a wide array of ages and geographical locations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 90% of the people received methylphenidate free of charge [27]. 58% of the students who misuse stimulants Lifetime prevalence: 55% thought it was easy to obtain them [23].…”
Section: Source Of Supply Of Methylphenidatementioning
confidence: 99%